Providing psychological support to people in intensive care: development and feasibility study of a nurse-led intervention to prevent acute stress and long-term morbidity. Issue 7 (23rd July 2018) - Wade, Dorothy; Als, Nicole; Bell, Vaughan; Brewin, Chris; D'Antoni, Donatella; Harrison, David A; Harvey, Mags; Harvey, Sheila; Howell, David; Mouncey, Paul R; Mythen, Monty; Richards-Belle, Alvin; et al.
Abstract : Objectives: Adverse psychological outcomes, following stressful experiences in critical care, affect up to 50% of patients. We aimed to develop and test the feasibility of a psychological intervention to reduce acute stress and prevent future morbidity. Design: A mixed-methods intervention development study, using two stages of the UK Medical Research Council framework for developing and testing complex interventions. Stage one (development) involved identifying an evidence base for the intervention, developing a theoretical understanding of likely processes of change and modelling change processes and outcomes. Stage two comprised two linked feasibility studies. Setting: Four UK general adult critical care units. Participants: Stage one: former and current patients, and psychology, nursing and education experts. Stage two: current patients and staff. Outcomes: Feasibility and acceptability to staff and patients of content and delivery of a psychological intervention, assessed using quantitative and qualitative data. Estimated recruitment and retention rates for a clinical trial. Results: Building on prior work, we standardised the preventative, nurse-led Provision Of Psychological support to People in Intensive Care (POPPI) intervention. We devised courses and materials to train staff to create a therapeutic environment, to identify patients with acute stress and to deliver three stress support sessions and a relaxation and recovery programme to them. 127 awake, orientated patients took part in an intervention feasibility study in two hospitals. Patient and staff data indicated the complex intervention was feasible and acceptable. Feedback was used to refine the intervention. 86 different patients entered a separate trial procedures study in two other hospitals, of which 66 (80% of surviving patients) completed questionnaires on post-traumatic stress, depression and health 5 months after recruitment. Conclusion: The 'POPPI' psychological intervention to reduce acute patient stress in critical care and prevent future psychological morbidity was feasible and acceptable. It was refined for evaluation in a cluster randomised clinical trial. Trial registration number: ISRCTN61088114; Results.